2020
DOI: 10.1186/s12887-020-02094-w
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among children under five years admitted for routine care of severe acute malnutrition: a prospective cohort study from Kampala, Uganda

Abstract: Background: Mortality among children under 5 years of age admitted to malnutrition units in sub-Saharan Africa remains high. The burden of HIV infection, a major risk factor for mortality among patients with severe acute malnutrition (SAM), has reduced due to concerted prevention and treatment strategies. None the less, anecdotal reports from the malnutrition unit at Uganda's National Referral Hospital (NRH) indicate that there is high mortality among patients with severe acute malnutrition (SAM) in routine ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
2
11
1
Order By: Relevance
“…Malnutrition was the leading underlying cause of death among HIV-uninfected decedents but was more frequent in the causal chain of HIV-infected decedents as HIV disease with wasting syndrome or as morbid conditions. This finding is in line with recent studies from Asia and Uganda that reported increased mortality among HIV-infected children who have severe acute malnutrition [52,53]. The increased risk of death could be because of the synergistic immunosuppressive effects of both diseases rendering the child vulnerable to fatal infections.…”
Section: Discussionsupporting
confidence: 91%
“…Malnutrition was the leading underlying cause of death among HIV-uninfected decedents but was more frequent in the causal chain of HIV-infected decedents as HIV disease with wasting syndrome or as morbid conditions. This finding is in line with recent studies from Asia and Uganda that reported increased mortality among HIV-infected children who have severe acute malnutrition [52,53]. The increased risk of death could be because of the synergistic immunosuppressive effects of both diseases rendering the child vulnerable to fatal infections.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis also indicated the causes of malnutrition among different under-five age groups: aged 0-23 months who were not breastfed within 1 h of birth; did not continue breastfeeding up to 6 months; and who were not fed an acceptable diet during 6-23 months of age. These findings are comparable to the other studies that investigated the malnourishment in under-five children in urban households (Ahsan et al 2017;Billah et al 2017;Gavhi et al 2020;Nalwanga et al 2020). Concerning nutritional services use, the number of children [aged 6-23 months] consumed Micro-Nutrient Powder and the children [aged 0-59 months] screened for nutrition status at facility and community levels were lower (0.02 to 0.05) in our both study areas, and the rates were lowest in Kashimpur.…”
Section: Discussionsupporting
confidence: 85%
“…More recent studies, in 2013 and 2017, at the unit have reported an HIV prevalence among the severely malnourished children of 24 and 12%, respectively. In these studies, a much higher mortality was observed among the CLHIV (33 and 47%, respectively) than in the CHUU (5 and 22%, respectively) (4,10). The mortality rate among the CHEU in the 2017 study was 36% (4).…”
Section: Introductionmentioning
confidence: 85%
“…In these studies, a much higher mortality was observed among the CLHIV (33 and 47%, respectively) than in the CHUU (5 and 22%, respectively) (4,10). The mortality rate among the CHEU in the 2017 study was 36% (4). Mortality therefore was more similar in CHEU and CLHIV than in CHUU.…”
Section: Introductionmentioning
confidence: 85%